Platform Session – Electroencephalography/Epilepsy: Clinical characteristics and outcomes of pediatric super refractory status epilepticus. (May 2018) - Vasquez, Alejandra; Farias-Moeller, Raquel; Fernández, Iván Sánchez; Abend, Nicholas S.; Anderson, Anne; Nicholas Brenton, J.; Clark, Justice; Glauser, Tracy; Goldstein, Joshua; Goodkin, Howard P.; Lai, Yi-Chen; McDonough, Tiffani L.; et al.
Abstract : Introduction: There is limited literature on pediatric super refractory status epilepticus (SRSE). We aimed to identify clinical variables associated with the occurrence of SRSE and to describe variability in SRSE treatment in a cohort of children admitted to pediatric intensive care units (ICU) with refractory status epilepticus (RSE). Methods: This prospective, observational study was performed at 14 US hospitals. Inclusion criteria: (1) hospital admission between June 2011 and September 2017, (2) convulsive RSE defined as focal or generalized convulsive seizures at onset that continued after administration of at least 2 anti-seizure drugs (ASDs), including one non-benzodiazepine ASD or use of continuous infusion (CI) and (3) age 1 month to 21 years. We divided the cohort into SRSE and non-SRSE groups. SRSE was defined as continuous or intermittent seizures lasting ⩾ 24 h following initiation of CI. We used Fisher's exact test and Wilcoxon rank sum test in the univariate analysis. Results: The initial cohort included 264 patients with a median (p25–p75) age of 4 (1.23–9.50) years. Thirty-five patients (19 males) were identified as SRSE cases, with a median age of 4.5 (1.91–8.45) years. Univariate analysis did not show significant differences between the groups for: sex, age, etiology, prior SE, diagnosis of epilepsy, in-hospital seizure onset, generalized tonic-clonic seizures or continuous SE. SRSE patients had delayed first line treatment initiation (71(15–135.5) vs. 16(5–40.5) min; p = 0.017), longer ICU stay (17(9–42) vs. 3(1.86–8.66) days; p < 0.001), higher rate of hypotension (17/35 (48.57%) vs. 59/229 (25.76%) patients; p = 0.029), lower proportion of return to baseline function at hospital discharge (8/35 (22.85%) vs. 168/229 (73.36%) patients; p < 0.001) and higher in-hospital mortality (6/35 (17.14%) vs. 4/229 (1.74%); p = 0.002) in comparison to the non-SRSE group. Within the SRSE group, resolution of SE was attained with a single CI in 48.57% (17/35) of the patients, 34.28% (12/35) with 2, and 17.14% (6/35) with 3 or more. Thirty-three (94.28%) of the SRSE patients received midazolam as first choice and 2/35 (5.71%) received pentobarbital. The most common 2nd CIs were: pentobarbital (66.66%), ketamine (11.11%), propofol (11.11%), midazolam (5.55%) and valproic acid (5.55%). Twenty of 35 (57.14%) patients received additional treatments, most commonly: corticosteroids (70%), ketogenic diet (55%), intravenous immunoglobulin (40%) and vagus nerve stimulation (25%). Conclusion: SRSE patients had delayed first-line treatment administration in comparison to non-SRSE patients. Once SRSE was established, children had significantly higher morbidity and mortality. Treatment approaches were heterogeneous, probably reflecting limited evidence to guide clinical decision-making in SRSE. (Funded by the Pediatric Epilepsy Research Foundation and Epilepsy Research Fund ).